AI-Driven Feedback Systems Reduce Sidewalk Riding on Shared E-Scooters - Mohammad Mehdi Oshanreh; Daniel Malarkey; Don MacKenzie (Findings)
This study examines the impact of AI-based feedback and speed restrictions on reducing sidewalk riding in shared e-scooters. In partnership with Spin, 100 scooters in Santa Monica, California were fitted with computer vision, with feedback features activated on half. Data from 488 trips revealed that feedback-equipped scooters spent 22% less time and 20% less distance on sidewalks. Nearly half of riders used sidewalks for less than 10% of their trip, while around 10% spent over 60% of trip time on sidewalks, regardless of feedback. These results suggest AI feedback modifies behavior but doesn't fundamentally change diverse riding patterns.